Ostiomeatal complex inflammation with a rare ethmoid sinolith utilizing cone-beam computed tomography: a clinical and radiological approach to diagnosis - Nurrachman, Aga Satria; Abdul Rahman, Fadhlil Ulum; Sarifah, Norlaila; Ghazali, Ahmad Badruddin; Epsilawati, Lusi (University of Washington, Elselvier, 2023)
A 28-year-old female patient was referred for panoramic radiography during a regular dental check-up. The dentist pointed out an additional suspicion of odontogenic maxillary sinusitis as she had complained of nasal obstruction, nasal discharge, postnasal drip, and frontal headache at the time. In this present case, cone-beam computed tomography (CBCT) imaging modality was utilized to evaluate the paranasal sinuses and detect any pathologic signs. This study aims to highlight the potential value of the modality for the identification of paranasal sinus diseases by presenting a rare finding of an ethmoid sinolith associated with a persistent ostiomeatal complex inflammation. The insufficient data currently available on the incidence of ethmoid sinoliths emphasize the significance of reports intended to inform practitioners about the imaging properties of these calcifications. To the author’s knowledge, this is the first case report that demonstrated the primary utilization of dental CBCT in detecting ethmoid sinolith in a straightforward manner